"I Guess They're All Real Moms Then": Constructing Motherhood Through Language in the Adoption Community. Issue 4 (2nd October 2019) - Weller, Melissa Rizzo
Abstract: Language used to construct motherhood varies, not only among groups inside and outside the adoption community, but among members of each group, as well. Some language is used to clarify relationships in adoptive families, but sometimes language can be stigmatizing, either intentionally or unintentionally. This study is a content analysis examining the construction of motherhood through language in 84 blogs written by adoptees, adoptive mothers, and birth mothers. Findings include a significant difference in the use of the term mother, in that birth mothers were more likely to use mother (or a form of it) in their blogs than were adoptees or adoptive mothers. Implications of this study are discussed, including practices to reduce the stigmatization of adoptive motherhood.